La reproducción del machismo y su influencia en la violencia basada en género, en el asentamiento humano Nuevo Indoamérica del distrito La Esperanza, provincia de Trujillo, región La Libertad - 2017 - Acosta Rodríguez, Daisy Jacqueline (2017)
The objective of this research was to explain the influence of the reproduction of machismo on gender - based violence in the New Indo - American Human Settlement, of La Esperanza District, Province of Trujillo, Region La Libertad - 2017, thus providing data to understand its Direct influence of the independent variable on the dependent variable. For this, the type of explanatory research was used; Methods such as ethnographic-ethnological, analytic-synthetic, inductive-deductive, and statistical; Techniques such as direct observation, participant observation and interviews; Instruments such as the questionnaire, the field book and the camera; Which served to analyze the perceptions of the 24 women living in the New Indo-American Human Settlement during the months of April, May, June and July of the year 2017. The main results of the investigation refer to the beliefs and behaviors machismo reproduced by the women themselves, the history of violence, where they were victims and witnessed violence in their childhood, the types of violence such as psychological, physical and sexual On the part of their partners, and the legitimacy of gender-based violence where they are natural and self-justifiable, remaining in a state of inferiority against the superior power of the male; Thus confirming the hypothesis about the reproduction of machismo and its influence on gender-based violence through the perpetuation of beliefs and behaviors that maintain male domination and the subordination of women from generation to generation.